Legislative Quotas and the Gender Gap in Campaign Finance: The Case of the 2014 and 2018 Legislative Elections in Colombia. (8th May 2023) - Maddens, Bart; Muyters, Gertjan; Put, Gert-Jan
ABSTRACT: Earlier empirical research on party list proportional representation systems shows that women spend less on campaigns than men, particularly when quotas are applied. An analysis of the candidate campaign expenses for the 2014 and 2018 Colombian Lower Chamber elections provides a novel test of this gender gap and its underlying causes. The research design leverages Colombia's unique context of electoral institutions, with interdistrict variation in terms of quota rules, and the availability of detailed information on campaign spending and funding. The regression models show that the gender gap in campaign spending is limited to districts with quota rules and disappears among incumbents and candidates listed first on the ballot. As for funding, women candidates are most disadvantaged with regard to personal funds and corporate donations but attract as many individual donations as men do.